(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2022)
The study aimed to evaluate the hydraulic conductivity using soil samples with undisturbed structure in the soil layers of 0-5, 5-10, 10-20, and 20-40 cm; 120 soil samples were collected. For the determination of hydraulic conductivity, the constant load permeameter was used. For geostatistical analysis, exploratory data analysis was performed using frequency histograms, determining the main measures of position and dispersion, verifying the trends for the construction of boxplot graphics, which allows the identification of discrepant points. The lowest and highest hydraulic conductivity values were found in the 20-40 cm and 0-5 cm soil layers, respectively; values commonly found in soils under forest conditions. Based on the results, we conclude when the soil sampling for analysis of hydraulic conductivity is random, the minimum distance between the points must be greater than 15.5 m.